Health-Related Quality of Life in Patients with Ankylosing Spondylitis: Relationship with Disease-Related Variables - Elolemy, Gehan; Aboughanima, Ahmed; Ganeb, Sahar; Elziat, Haytham (Current Rheumatology Reviews, 2020)
Background: Ankylosing spondylitis (AS) is a chronic progressive inflammatory disease leading to functional limitations and subsequently impaired quality of life (QoL). Despite the fact that QoL was recognized as a significant perception, it was excluded from the core domains (defined by the Assessment of Spondyloarthritis International Society), because of ambiguity of measurement choice. Aim: To assess QoL in patients with AS using a generic; Short Form-36 (SF-36) and a diseasespecific; Ankylosing Spondylitis quality of life (ASQoL) instruments and to explore its relationship to the clinical characteristics, disease activity, functional status, and radiographic severity. Methods: A total of 47 AS patients who fulfilled modified New York criteria were included. Disease activity, functional status, spinal mobility, and radiographic severity were assessed by Bath AS Disease Activity Index (BASDAI), Bath AS Functional Index (BASFI), Bath AS Metrology Index (BASMI) and Bath AS Radiology Index (BASRI) respectively. SF-36 and ASQoL instruments evaluated Qol. Results: Physical health was more affected especially in patients with peripheral arthritis by SF-36 (p=0.008) and ASQoL (p=0.022) scores. Both SF-36 total and ASQoL scores correlated significantly with BASDAI (r = -0.329, p = 0.024 and r = 0.420, p = 0.003), BASFI (r = -0.399, p = 0.005 and r = 0.513, p=0.001) and BASMI (r = -0.382, p = 0.008 and r = 0.482, p= 0.001) respectively. Conclusion: QoL was impaired in AS patients with highest impact on physical health especially in association with peripheral arthritis. SF-36 and ASQol have a comparable achievement in the evaluation of QoL in AS patients and both physical function and spinal mobility were identified as predictors of poor QoL.
Keywords: BASFI